NUTRITIONAL STATUS OF UNDER FIVE CHILDREN IN AN URBAN SLUM - DR. MALLIKARJUN K BIRADAR M.D. (International Journal of Pharma and Bio Sciences, 2013)
Nutrition is the cornerstone of socioeconomic development of a country. Malnutrition is one of the most common causes of morbidity and mortality in children. The objective was to determine the nutritional status of under five children. Community based cross-sectional study was conducted from February to April 2010 in under five children in an Urban slum in Raichur. 104(10.6%) children were found to be malnourished, out of them 25(2.5%) were found to be severely malnourished. Children with lower socio-economic status were found to be severely malnourished. Emphasis should be given on maternal nutrition and their education, and improving the socio-economic status wil reduce the burden of under nutrition in children. The present study also help the policy planners to develop strategies to combat different forms of malnutrition by targeting the high-risk groups.